The complex relation between access to opioid agonist therapy and diversion of opioid medications: a case example of large-scale misuse of buprenorphine in the Czech Republic - Viktor Mravčík; Barbara Janíková; Barbora Drbohlavová; Petr Popov; Alessandro Pirona (BMC, 2018)
Abstract Opioid agonist therapy (OAT) has been available in a standard regime in the Czech Republic since 2000. Buprenorphine is the leading medication, while methadone is available only in a few specialised centres. There is an important leakage of buprenorphine onto the illicit market, and the majority of Czech opioid users are characterised by the misuse (and injecting) of diverted buprenorphine medications. Most prescribed buprenorphine for OAT is not covered by current national health insurance schemes, and patients have to pay considerable prices to afford their treatment. This affordability barrier together with limited accessibility is likely the leading factor of limited coverage of OAT and of recent stagnation in the number of patients in the official treatment programmes in the Czech Republic. It also encourages doctor shopping and the re-selling of parts of their medication at a higher price, which represents the main factor that drives the Czech illicit market for buprenorphine, but at the same time co-finances the medication of clients in official OAT programmes. Improving access to OAT by making it financially affordable is essential to further increase OAT coverage and is one of the factors that can reduce the illicit market with OAT medications.